Another puzzle piece in the systematics of the chewing louse genus Myrsidea, with a description of a new genus Apomyrsidea - Kolencik, Stanislav; Sychra, Oldřich; Allen, Julie M. (European Journal of Taxonomy, 2021)
A new avian chewing louse genus Apomyrsidea gen. nov. is described based on species parasitizing birds in the family Formicariidae. Diagnostic characteristics and phylogenetic analyses were used to evaluate and confirm the generic status and merit its recognition as unique and different from Myrsidea Waterston, 1915. Three species previously belonging to the genus Myrsidea are placed in the new genus Apomyrsidea gen. nov. and are discussed: Apomyrsidea circumsternata (Valim & Weckstein, 2013) gen. et comb. nov., Apomyrsidea isacantha (Valim & Weckstein, 2013) gen. et comb. nov. and Apomyrsidea klimesi (Sychra in Sychra et al., 2006) gen. et comb. nov.